The Deesis Composition in the Decoration System of the Byzantine Templon of the 12th — Early 13th Centuries - Obraztsova, Kseniia B. (Actual Problems of Theory and History of Art, 2017)
The article is focused on the problem of the determination of the place of the Deesis compositionin the system of the 12th — early 13th century Byzantine sanctuary screen. The Deesis is among the crucial subjects in the decoration of a templon, though the representation of it did not take a stable form and position ona screen in the period under review. The article surveys variants of representing the theme of the Deesis in the diverse types of sacred images included in the ensemble of a sanctuary screen as the evidence of a composition search. The most forward-looking type of them turned out to be the series of Deesis icons on separated panels.The paper examines the possibility that they were situated on the templon beams that became a prototype forthe Deesis row of the iconostasis screen.